COVID-19 pandemic impact on people with diabetes: results from a large representative sample of Italian older adults - Vigezzi, Giacomo Pietro (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2022)
Restrictions imposed to prevent SARS-CoV-2 transmission should be weighed against consequences on vulnerable groups’ health. Lifestyles and disease management of older people with diabetes might have been differentially impacted compared to non-chronic individuals.